Doświadczenia rodzica dziecka z Centralnym Zaburzeniem Przetwarzania Słuchowego. Studium przypadku - Antosik-Kot, Nikola (Studia Edukacyjne, 2025)
Central Auditory Processing Disorder (CAPD) has gained wider recognition relatively recently. The article titled “The Experiences of a Parent of a Child with Central Auditory Processing Disorder and an Opinion on the Effectiveness of the FM System: A Case Study of a Sixteen-Year-Old Boy” offers an analysis of theoretical content, including definitions and conclusions regarding CAPD, its symptoms, causes, diagnostic procedures, and therapeutic interventions. The cognitive and scientific interest of the author was sparked by the individual case of a sixteen-year-old boy. Therefore, the case study section focuses on the subjective-objective experiences of the parent of a child diagnosed with CAP- Disorder in 2017, as well as the parent’s opinion on the effectiveness of the FM system used by the boy.